TOXICITY TEST OF ROSELLE NANOHYDROXYAPATITE-GELATIN ON OSTEOBLASTS CELLS USING MTT ASSAY - Pakpahan, Evie Lamtiur (Universitas prof. Dr. Moestopo (Beragama), 2025)
Background: Orthodontic treatment often results in a relapse of tooth position after appliance removal due to insufficient bone remodeling. Effective prevention requires controlling inflammation and enhancing osteoblast activity to promote new bone formation and stabilization. Roselle calyx extract contains flavonoids with anti-inflammatory and antioxidant properties, while nanohydroxyapatite combined with gelatin improves scaffold porosity, cell adhesion, and biodegradability, thereby enhancing bone bioactivity. Methods: This in vitro study evaluated the cytocompatibility of nanohydroxyapatite–gelatin–roselle (NanoHAp-Gel-RE) composite on osteoblasts using an MTT assay. Data were analyzed for normality using the Shapiro–Wilk test, followed by one-way ANOVA and Tukey’s HSD post hoc test to determine differences between treatment groups. Results: Cell viability analysis showed that NanoHAp-Gel-RE at concentrations of 15%, 20%, 25%, and 30% resulted in viability values of 90.71%, 112.38%, 117.96%, and 117.34%, respectively. All tested concentrations demonstrated viability greater than 50%, indicating no cytotoxic effects. Conclusion: Roselle calyx extract and NanoHAp-Gel-RE composite exhibit good cytocompatibility toward osteoblast cells. Their ability to enhance cell viability suggests the potential for application as biocompatible therapeutic materials to support bone remodeling in preventing post-orthodontic relapse.